THE IMPACT OF REGIONAL ECONOMIC INTEGRATION ON CHINESE BUSINESSES: NAVIGATING NEW DYNAMICS - Ferrara, Marco; Sánchez, Elena (International Journal of Contemporary Research in Marketing and Management Sciences, 2024)
Regional economic integration is a global economic development pattern in which countries within a specific region unify their economic activities and, in some cases, cede economic sovereignty. This phenomenon has garnered significant attention from Chinese scholars who have explored its multifaceted impacts. Research by Wei Xiong (2023) has revealed that regional economic integration positively influences enterprise innovation, shedding light on its potential benefits. Ren-wen Mu and Xu Zhao (2023) have illustrated how regional economic integration can enhance member countries' economic growth by dismantling trade barriers, eliminating cross-border market impediments, and fostering the creation of a unified market. Furthermore, Hui-zi Liu (2022) has investigated the effects of regional economic integration on international trade, finding that while it can stimulate international trade, it may also impede trade for nonregional countries due to trade barrier restrictions. In the context of China-ASEAN relations, Yan-hua Gong and Yuan Gong (2022) have examined economic development using the Southeast Asian segment of the Trans-Asian Railway as a case study. Their research has shown that regional economic integration serves as a potent catalyst for economic growth in the China-ASEAN region. This abstract provides an overview of the intricate research landscape on regional economic integration and its implications, highlighting its potential for fostering innovation, economic growth, and international trade.